Modeling of the Turbulent Plasma Sheet During Quiet Geomagnetic Conditions - Stepanova, M (2011)
Recent studies have shown the importance of turbulent processes in the Earth magnetosphere dynamics, including the plasma sheet stability. In this study, turbulent eddy-diffusion coefficients were derived using the Cluster satellite data. The corresponding values of dawn-dusk electric field potential were obtained from the SuperDarn measurements. These results confirm the theory of the turbulent plasma sheet formation proposed by Antonova and Ovchinnikov (1996, 1999, 2001). According to this theory, a compact and comparatively stable turbulent plasma sheet is formed when the regular plasma transport related to the dawn-dusk electric field across the plasma sheet is compensated by the eddy-diffusion turbulent transport. Our results have shown that this theory reproduces the dynamics of the turbulent plasma sheet, including its thickness. © 2011 Elsevier Ltd.